2021
DOI: 10.1177/00031348211048849
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vaping on Primary Spontaneous Pneumothorax Outcomes

Abstract: Introduction Cigarette smoking is associated with primary spontaneous pneumothorax (PSP). Electronic cigarettes (E-cigarettes) are touted as a healthier alternative to cigarettes; however, the impact E-cigarette use has on PSP management is not known. The goal of this study was to determine if E-cigarette use is associated with inferior outcomes after PSP, compared to never smokers and cigarette smokers. Methods We conducted a retrospective cohort study of patients in a large tertiary care hospital system in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…]3 cm, should undergo lung expansion with placement of a chest tube or catheter (10). In one study, all e-cigarette using patients with spontaneous pneumothorax required tube thoracostomy (11). VATS is a minimally invasive technique that can be used with blebectomy and/or pleurodesis.…”
Section: Discussionmentioning
confidence: 99%
“…]3 cm, should undergo lung expansion with placement of a chest tube or catheter (10). In one study, all e-cigarette using patients with spontaneous pneumothorax required tube thoracostomy (11). VATS is a minimally invasive technique that can be used with blebectomy and/or pleurodesis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the American College of Chest Physicians, a large pneumothorax, defined as ≥3 cm, should undergo lung expansion with placement of a chest tube or catheter 11 . In one study evaluating the need for tube thoracostomy in different types of smokers with pneumothorax, all e‐cigarette‐using patients with spontaneous pneumothorax requiring tube thoracostomy 12 . VATS is a minimally invasive technique that can be used with blebectomy and/or pleurodesis.…”
Section: Discussionmentioning
confidence: 99%
“…11 In one study evaluating the need for tube thoracostomy in different types of smokers with pneumothorax, all e-cigarette-using patients with spontaneous pneumothorax requiring tube thoracostomy. 12 VATS is a minimally invasive technique that can be used with blebectomy and/or pleurodesis. Blebectomy is a procedure to remove air blebs from the lung while pleurodesis adheres to the lung tissue to the chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…It is categorized into Primary Spontaneous Pneumothorax (PSP) and Secondary Spontaneous Pneumothorax (SSP), and the cause of Primary Spontaneous Pneumothorax is still unknown [2] . Some studies have shown that cigarette smoking, marijuana use [3,4] , changes in atmospheric pressure, air pollution [5,6] , high lean body mass, low body mass index (BMI), are closely associated with SP [7] . Secondary spontaneous pneumothorax is often associated with underlying lung diseases, commonly chronic obstructive pulmonary disease (COPD) [8] , cystic pulmonary fibrosis (CPF) [9] , lung tumors, and lung infections [10] .…”
Section: Introductionmentioning
confidence: 99%